PENANGANAN NEGATIF CIRCLE DI PESANTREN - Marwiyah, Syarifatul; Dasuki, Mohammad; Nafi’ah, Khoyyir Nuron; Aini, Ida Zulfa; Yulifah, Yulifah; Wardani, Nuriyah; Himmah, Faiqotul; Kamilah, Wardatul; Marfu’ah, Siti Sururun; Fathiyah, Hilwi Asna; Putri, Sasa Amelia; Zulkarnaein, Safira Rizki; Fitriah, Lailatul; Afiati, Zahro Arum; Ati, Anggun Cahyaning; Nazila, Ilma Ainun; Fajariyah, Lailatul Khoirotul; Azzahra, Aura Fatimah; Sadatunnisa’, Aisyatul Itho’ah; Nisa, Fatma Zahrotun; Maulidia, Arini (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
The phenomenon of negative circles at Pondok Pesantren Assunniyyah Putri Kencong Jember is reflected in student behaviors that are inconsistent with pesantren values, such as staying up late, low discipline, and poor dormitory cleanliness. This community engagement program aims to break these negative behavioral cycles through a Participatory Action Research (PAR) approach involving caregivers, supervisors, university students, and the santri. The PAR stages consisted of participatory inquiry, change-oriented action, and collective reflection, with an emphasis on emotional mentoring, positive habit formation, and strengthening role modelling within the dormitory setting. The program demonstrated significant improvements across several indicators. Students’ knowledge of pesantren rules increased from 50 to 75, while pro-discipline attitudes rose from 2.0 to 4.0. Behaviorally, the proportion of students sleeping before 22:00 increased from 40% to 75%, prayer attendance improved from 75% to 90%, and dormitory cleanliness rose from 40% to 80%. Weekly disciplinary violations declined from 10 cases to 4 cases, and caregiver satisfaction reached 75%. The main limitation of the program lies in the short monitoring period, which may not fully capture the long-term consistency of behavioral change. The PAR model has potential for replication in other pesantren contexts with contextual adjustments and stronger long-term monitoring mechanisms.